Research as a pedagogical strategy a step towards critical pedagogies for the 21st century (2011)
This research paper aims to promote the idea that the use of research in the fields of education and pedagogy is going to create a modification in these fields, as well as in the practical processes and actions that they have established. First of all, this paper provides a quick overview of the way in which education and pedagogy have been constituted in the Western, capitalist modern society, along with its paradigms, trends, concepts, methodological approaches, research areas and models. Next, this paper shows the way in which pedagogical thinking has been formed around research, that which gives rise to diverse methodological approaches which become the daily practice of educators. Finally, this paper closely examines one of these methodological lines, Research as a Pedagogical Strategy (Investigación como Estrategia Pedagógica - IEP), which emerged in the creation of the critical pedagogies developed in Latin American contexts, in dialogue with the emerging and dynamic approaches in different parts of the world.